Innovation and Productivity - Evidence from Six Latin American Countries - Gustavo Crespi; Pluvia Zuniga (Inter-American Development Bank (IDB), 2010)
This study examines the determinants of technological innovation and its impact on firm labor productivity across six Latin American countries (Argentina, Chile, Colombia, Costa Rica, Panama, and Uruguay) using micro data from innovation surveys. In line with the literature, in all countries firms that invest in knowledge are more able to introduce new technological advances, and those that innovate have greater labor productivity than those that do not. Yet firm-level determinants of innovation investment are much more heterogeneous than in OECD countries. Cooperation, foreign ownership, and exporting increase the propensity to invest in innovation activities and encourage innovation investment in only half of the countries studied. Scientific and market sources of information have little or no impact on firm innovation efforts, which illustrates the weak linkages that characterize national innovation systems in those countries. The results in terms of productivity, however, highlight the importance of innovation in enabling firms to improve economic performance and catch up.
Keywords: O12; O14; O31; O33; O40; 330; Innovation; Productivity; Developing countries; Latin America; Innovation surveys